Diagnostic ultrasound estimates of muscle mass and muscle quality discriminate between women with and without sarcopenia - Ismail, Catheeja; Zabal, Johannah; Hernandez, Haniel J.; Woletz, Paula; Manning, Heather; Teixeira, Carla; DiPietro, Loretta; Blackman, Marc R.; Harris-Love, Michael O. (Frontiers in Physiology, 2015)
Introduction: Age-related changes in muscle mass and muscle tissue composition contribute to diminished strength in older adults. The objectives of this study are to examine if an assessment method using mobile diagnostic ultrasound augments well-known determinants of lean body mass (LBM) to aid sarcopenia staging, and if a sonographic measure of muscle quality is associated with muscle performance. Methods: Twenty community-dwelling female subjects participated in the study (age = 43.4 ±20.9 years; BMI: 23.8, interquartile range: 8.5). Dual energy X-ray absorptiometry (DXA) and diagnostic ultrasound morphometry were used to estimate LBM. Muscle tissue quality was estimated via the echogenicity using grayscale histogram analysis. Peak force was measured with grip dynamometry and scaled for body size. Bivariate and multiple regression analyses were used to determine the association of the predictor variables with appendicular lean mass (aLM/ht2), and examine the relationship between scaled peak force values and muscle echogenicity. The sarcopenia LBM cut point value of 6.75 kg/m2 determined participant assignment into the Normal LBM and Low LBM subgroups. Results: The selected LBM predictor variables were body mass index (BMI), ultrasound morphometry, and age. Although BMI exhibited a significant positive relationship with aLM/ht2 (adj. R2 = .61, p < .001), the strength of association improved with the addition of ultrasound morphometry and age as predictor variables (adj. R2 = .85, p < .001). Scaled peak force was associated with age and echogenicity (adj. R2 = .53, p < .001), but not LBM. The Low LBM subgroup of women (n = 10) had higher scaled peak force, lower BMI, and lower echogenicity values in comparison to the Normal LBM subgroup (n = 10; p < .05). Conclusions: Diagnostic ultrasound morphometry values are associated with LBM, and improve the BMI predictive model for aLM/ht2 in women. In addition, ultrasound proxy measures of muscle quality are more strongly associated with strength than muscle mass within the study sample.